Effect of Interactive Supervision Training on Improving of Nursing Behavior in Prevention of Infection and Effective Communication - Rosina Leisubun; Asnet Leo Bunga; Sudibyo Supardi (Indonesian Journal of Health Research, 2019)
Introduction. Nurse behavior in prevention of infection and effective communicate aimed at minimizing arrows and maximizing patient safety. Implementation of nurse behavior can be realize by hand washing and communicate is effective and complete. To evaluate the associated behaviors of implementing nurses can be done by supervision method by chief of the room or nursing supervisor. This study aims to determine the effect of interactive supervision training on improving the behavior of nurses in prevention of infection: hand washing & effective communication. Methods. The research is a quantitative research with a quasi-experimental design using pre & post test design with a control group. The sample in the study was 17 supervisor and 70 nurse nurses. Interventions carried out are interactive supervision training for chief of the room & team leader/PJ Shift. Results. The result of the study found difference in behavior of nurses on hand washing & SBAR communication before & after training (p value=0,000) Further analysis shows a good influence between interactive supervision training on improving nurse performance in hand washing & SBAR communication compliance (p value=0,000). Conclusion. Expected to he carried out in a interactive supervision of all implementing nurses in an effect to improve safety of patients.